Treatment of periodontal infrabony defect using particulate dentin graft and recombinant human platelet-derived growth factor - Vishal Garg; Amit Bhardwaj; Kirti Chawla (Journal of Indian Society of Periodontology)
Periodontal bone defects pose significant challenges in dentistry, necessitating effective treatment strategies. This case report explores the regenerative potential of using a combination of particulate dentin graft (PDG) derived from extracted teeth and recombinant human platelet-derived growth factor (rhPDGF) as bone graft material for the treatment of human periodontal infrabony defects. A 44-year-old male patient presented with a 9 mm pocket probing depth (PPD) and an 8 mm infrabony defect depth mesial to #13, with no gingival recession (GR). Following Phase I therapy, open flap debridement and grafting with PDG and rhPDGF were performed. Clinical and radiographic measurements were taken at baseline and 6 and 12 months. At 12 months, a 6 mm reduction in PPD and clinical attachment level gain were observed with no GR. 5 mm (83.33%) bone fill was seen radiographically. Within the limitations of this case report, the utilization of PDG with rhPDGF for the treatment of infrabony periodontal defects has emerged as a promising regenerative therapy.